Effect of precooling on high intensity cycling performance. Issue 6 (1st December 1999) - Marsh, D; Sleivert, G
Abstract : OBJECTIVE: To examine the effects of precooling skin and core temperature on a 70 second cycling power test performed in a warm and humid environment (29 degrees C, 80% relative humidity). METHODS: Thirteen male national and international level representative cyclists (mean (SD) age 24.1 (4.1) years; height 181.5 (6.2) cm; weight 75.5 (6.4) kg; maximal oxygen uptake (VO2peak) 66.1 (7.0) ml/kg/min) were tested in random order after either 30 minutes of precooling using cold water immersion or under control conditions (no precooling). Tests were separated by a minimum of two days. The protocol consisted of a 10 minute warm up at 60% of VO2peak followed by three minutes of stretching. This was immediately followed by the 70 second power test which was performed on a standard road bicycle equipped with 172.5 mm powermeter cranks and mounted on a stationary ergometer. RESULTS: Mean power output for the 70 second performance test after precooling was significantly (p<0.005) increased by 3.3 (2.7)% from 581 (57) W to 603 (60) W. Precooling also significantly (p<0.05) decreased core, mean body, and upper and lower body skin temperature; however, by the start of the performance test, lower body skin temperature was no different from control. After precooling, heart rate was also significantly lower than control throughout the warm up (p<0.05). Ratings of perceived exertion were significantly higher than the control condition at the start of the warm up after precooling, but lower than the control condition by the end of the warm up (p<0.05). No differences in blood lactate concentration were detected between conditions. CONCLUSIONS: Precooling improves short term cycling performance, possibly by initiating skin vasoconstriction which may increase blood availability to the working muscles. Future research is required to determine the physiological basis for the ergogenic effects of precooling on high intensity exercise.